ANALISIS KESALAHAN SISWA SMP KELAS VII DALAM MENYELESAIKAN SOAL MATERI HIMPUNAN MELALUI PEMBELAJARAN DARING - Risti Amelia; M. Ghiyats Ristiana (IKIP Siliwangi, 2022)
The experimentation was conducted online with the aim of analyzing student errors when working on set material questions through bold learning. The subjects of the experimentation are students from private high school in Bandung City with total of 20 students. The collection of data method uses the Whatsapp Group media. The technique for this observation is descriptive qualitative. Research media uses 6 about descriptions. The conclusion from the inquiry of participants in working on sets of: (1) students cannot change a representation into other forms, (2) students also cannot identify the properties of the set concept. This study obtained the result that the completion of the set questions was difficult for students. So it can be concluded that the skill of students when learning is low about the set material is still categorized (minimal).